Rede de coautoria na produção científica : um estudo sobre a temática gênero em periódicos na Ciência da Informação - Silva, Morgana Linhares de Araújo (2024)
Examining the connection between scientific production and its authors provides an understanding of the intrinsic characteristics of the participants in a social network in which they are involved. This includes the research conducted, the elements that influence these interactions, the thematic interests of scientific investigations, the connection between different institutions and how areas strengthen and expand their collaborations in sharing knowledge for scientific advancement. This process is especially driven by the interdisciplinarity inherent to Information Science. Given the relationship of the theme “gender” in scientific production, the aim of this study is to map gender studies and their co-authorship networks in the scientific production of Information Science published in journals classified as Qualis A1 and A2. The social network analysis method, which focuses on the interconnection of actors and their relationships, plays a fundamental role in understanding these networks. The research is characterized by its descriptive level, providing an approximate overview of the theme in the scientific production on gender published in the journals TransInformação (A1); Information & Society: studies, Encontros Bibli, Informação & Informação, Perspectivas em Ciência da Informação and Em Questão (A2). Fortynine productions were retrieved using the “gender” search filter present in the title, keywords and/or abstract and using the last twenty years (2004-2023) as a time criterion. The results were represented in graphs, using the Gephi tool and the Excel® spreadsheet editor, in addition to tables and graphs. Thus, 105 actors, their academic backgrounds and institutional ties, in addition to 148 descriptors, were mapped, forming the thematic network on gender of these productions. The journals Informação & Informação and Em Questão presented the highest number of scientific productions on gender. The most frequent keywords on the topic were gender and organization of knowledge, and the clusters are mostly related to gender, information science, gender studies and female gender. The co-authorship network presents seven subgroups with different connectivity patterns. Central actors were identified as key connectors between different subgroups and the formation of clusters, low density in the network and few connections between actors were evidenced. Vital, L. P., Lima, I. F. and Viana, A. R. L. presents centrality of approximation and intermediation and degree of modularity. Regarding the gender of authorship, 68% are female authors and 32% are male authors, mostly trained in the area of IS and highlighting the institutional link with UNESP, USP, UNIRIO, UFSC and IBICT, among others, concentrated in the Southeast and South regions and a low density of production in the Central-West, North and Northeast regions. It contributes to revealing the co-authorship network on gender and its actors in Information Science and its scientific production, favoring relationships between actors and scientific fields and suggests the need to encourage collaborations.